ECTHR_COMMITTEE 21504/03 vom 23. Oktober 2012 , AFFAIRE TODIRICĂ ET AUTRES c. ROUMANIE - Ecthr Committee (2012)
Violation de l'article 6 - Droit à un procès équitable (Article 6 - Procédure civile;Article 6-1 - Délai raisonnable); Violation: 6;6-1